Edible coatings: A sustainable approach to protect perishable fruits and vegetables - Meghachitra, S; Sumathi, T; Irene, V P; Jeyakumar, P; Sharmila, R C (Plant Science Today, 2025)
Fruits and vegetables are crucial to a nutritious diet but are highly perishable, posing challenges in maintaining freshness during storage and transportation. This comprehensive review aims to provide insights into the influence of edible coatings on the postharvest preservation of fruits and vegetables. Edible coatings, made from natural polymers such as proteins, polysaccharides and lipids, have gained attention as an effective method to extend shelf life. These coatings form a protective barrier that reduces moisture loss, gas exchange and microbial growth, thereby delaying senescence and preserving quality attributes like firmness, colour, texture and nutritional content. Application methods include dipping, spraying and brushing to ensure uniform coverage. The efficacy of edible coatings depends on factors such as composition, concentration and specific characteristics of the produce. Additionally, incorporating antimicrobial agents like essential oils and plant extracts enhances food safety by inhibiting spoilage microorganisms. Beyond shelf life extension, edible coatings help reduce postharvest losses, improve marketability and decrease reliance on chemical preservatives and synthetic packaging. However, challenges related to formulation optimization, scalability, cost and consumer acceptance must be addressed to enable broader adoption. Overall, edible coatings offer a promising strategy for preserving fruits and vegetables, warranting further research to fully realize their potential in the food industry.